The Descriptive Epidemiology of Primary Lung Cancer in an Alberta Cohort with a Mutivariate Analysis of Survival to Two Years - Sandor J Demeter; Chester Chmielowiec; Wayne Logus; Pauline Benkovska-Angelova; Philip Jacobs; David Hailey; Alexander McEwan (Canadian Respiratory Journal)
BACKGROUND: Lung cancer contributes significantly to cancer morbidity and mortality. Although case fatality rates have not changed significantly over the past few decades, there have been advances in the diagnosis, staging and management of lung cancer.